Blik op de Stadswal, Gorcum. (Dordrecht : Nederlandse Kring van Beeldhouwers, 1982)
van Dijk, Jan Asjes ; Teeuwen, Marry ; van Bennekum, Henk ; van Gulik, Cor ; Hilgemann, Ewerdt ; Leeuwenburgh, Jane ; Teeuwen, Roel ; Den Arend, Lucien ; Timmer, Jan ; Glandorf, Maria
Blik op de stadswal, Gorcum, 28.5 - 4.9.1982
boek